Respuesta :

Space

Answer:

[tex]y'= \frac{3x+2}{2\sqrt{x} }[/tex]

General Formulas and Concepts:

Calculus

The derivative of a constant is equal to 0

Basic Power Rule:

  • f(x) = cxⁿ
  • f’(x) = c·nxⁿ⁻¹

Product Rule: [tex]\frac{d}{dx} [f(x)g(x)]=f'(x)g(x) + g'(x)f(x)[/tex]

Chain Rule: [tex]\frac{d}{dx}[f(g(x))] =f'(g(x)) \cdot g'(x)[/tex]

Step-by-step explanation:

Step 1: Define

[tex]y=\sqrt{x} (x+2)[/tex]

Step 2: Rewrite

[tex]y=x^{\frac{1}{2} } (x+2)[/tex]

Step 3: Differentiate

  1. Product Rule [Basic Power/Chain Rule]:                 [tex]y'= \frac{1}{2} x^{\frac{1}{2} -1}(x+2)+x^{\frac{1}{2} }(1)[/tex]
  2. Simplify:                                                                            [tex]y'= \frac{1}{2} x^{\frac{-1}{2}}(x+2)+x^{\frac{1}{2}}[/tex]
  3. Rewrite:                                                                                        [tex]y'= \frac{x+2}{2\sqrt{x} } + \sqrt{x}[/tex]
  4. Add:                                                                                                       [tex]y'= \frac{3x+2}{2\sqrt{x} }[/tex]